Energy dysfunction in humans: the obesity syndrome - Speechly, David Paul (My University, 2014)
Hyperphagia, rather than reduced energy expenditure, is generally accepted to be the main cause of obesity. As such, the disruption of the appetite-satiety mechanism has been blamed for the relative excess in energy intake that is characteristic of the obese. Factors affecting appetite regulation, and the causes of this dysregulation in the obese remain to be established. Putative mechanisms regulating the physiology of appetite include concentrations of various hormones and macronutrient content. These, in turn, may be influenced by meal frequency, and different hormonal and appetite responses to these changes in meal frequency may be evident in the lean and obese. In an attempt to elucidate the link between the observed incidence of obesity and elevated serum insulin concentration, I examined in a controlled setting, the effects of altered feeding frequencies, varied energy intake and changes in macronutrient composition on appetite control and insulin concentration in lean and obese males. Furthermore the correlation between serum insulin concentrations immediately before a meal and energy intake was also investigated, as was the incidence of fasting hyperinsulinaemia with concomitant euglycaemia in non-diabetic Caucasian South African adults and its relationship to BMI (Body Mass Index).